PENGARUH KETAATAN TERHADAP PERATURAN PERUNDANGAN, PEMANFAATAN TEKNOLOGI INFORMASI, PENGENDALIAN AKUNTANSI DAN KOMPETENSI APARATUR PEMERINTAH DAERAH TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (AKIP) (Studi Empiris Pada Satuan Kerja Perangkat Daerah - Razi, Riska Fahrul; Savitri, Enni; ', Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
the research aims to analyze of influencing the adherence of the law regulation, information technology utilization, accounting control and competency of human resources in government to performance accountability. Object of this research is department of SKPD Indragiri Hulu. There are ninety seven questionnaires were sent, but only eighty eight questionnaires are returned. That data are analyzed by linear regression method and SPSS program version 19. The results of this research showedadherence of the law regulation has an effect toperformance accountability with 0,000 significance, information technology utilization has an effect toperformance accountability with 0,000 significance, accounting control has an effect to performance accountability with 0,005 significance and competency of human resources has an effect toperformance accountability with 0,000 significance. The results of this research also showed that coefficient R square is 82,9%. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well. While the remaining influenced by other variables not included in the regression models were not included in this study. All variables also have strong relation with variable dependents in this research.Keywords: adherence of the law, information technology utilization, accounting control, and competency of human resources, performance accountability